A heuristic fuzzy algorithm for assessing and managing tourism sustainability - Andria, Joseph; di Tollo, Giacomo; Pesenti, Raffaele (Soft computing (Berlin, Germany), 2020)
“Smartness” and “sustainability” are gaining growing attention from both practitioners and policy makers. “Smartness” and “sustainability” assessments are of crucial importance for directing, in a systemic perspective, the decision-making process toward sustainability and smart growth objectives. Sustainability assessment is a major challenge due to the multidisciplinary aspects involved that make the evaluation process complex and hinder the effectiveness of available monitoring tools. To achieve the assessment objective, we introduce an enhanced fuzzy logic-based framework for handling the inherent uncertainty and vagueness of the involved variables: we apply our approach to Italy, and we compare it with two other sustainability methodologies. We also perform a correlation analysis to assess the relationship between our ranking results and the attained quality of life scores. Our approach ensures a high level of versatility that makes its use possible jointly with (or alternatively to) other existing methodologies such as the Global Sustainable Tourism Council Criteria and the United Nations World Tourism Organization destination-level indicators.